Penerapan Pengendalian Kalitas Produk Kaleng Kemasan Crab Meat 800ml Menggunakan Metode SIX Sigma Pendekatan DMAIC - Tomi Parianggara; Subchan Asy’ari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Packaging can manufacturers experience a quality problem, namely with product defects / defects in every production that has not reached zero defects, especially in 800 ml crab meat packaging cans which most often experience product defects. Six Sigma can be defined as a methodology that functions for process improvement that aims to minimize defect processes and improve production quality using the DMAIC (Define, Measure, Analize, Improve, Control) approach. So that it can be analyzed from the known problems to obtain improvement recommendations. From the results of the measurement of the data obtained that for (CTQ) Critical to Quality, the key is based on the pareto diagram, that 85% of the highest defects are in the breaking of welding. From the analysis of the causal diagram, the factors that cause product defects / defects come from machine, human, raw material, and environmental factors. Thus, recommendations can be made for appropriate corrective actions, especially providing training and direction for employees on how to work according to SOPs for checking raw materials, improving the quality standards of raw materials received, and adding appropriate lighting during the production process so that defects / production defects can be minimized.